2016
DOI: 10.1016/j.amjmed.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization of Gastric Antral Vascular Ectasia: A Potential Manifestation of the Metabolic Syndrome

Abstract: These results confirm the association of gastric antral vascular ectasia with underlying cirrhosis and revealed a significant correlation of gastric antral vascular ectasia with features of metabolic syndrome such as diabetes, BMI, vascular disease, and nonalcoholic steatohepatitis cirrhosis. The pathophysiology of gastric antral vascular ectasia remains uncertain, but we speculate that it may be a manifestation of the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Additionally, patients with GAVE are known to have higher recurrence of bleeding after endoscopic intervention, and blood loss in these patients may continue for a chronic duration. Literature reports that up to 62% of patients with GAVE may remain transfusion dependent [ 16 ]. Hence, we believe that it is imperative to identify patient demographics and establish risk factors for GAVE hospitalizations to design a robust management plan to reduce morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, patients with GAVE are known to have higher recurrence of bleeding after endoscopic intervention, and blood loss in these patients may continue for a chronic duration. Literature reports that up to 62% of patients with GAVE may remain transfusion dependent [ 16 ]. Hence, we believe that it is imperative to identify patient demographics and establish risk factors for GAVE hospitalizations to design a robust management plan to reduce morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, a retrospective cohort study by Smith et al on 135 patients revealed a significant correlation of GAVE with liver disease, diabetes mellitus, body mass index (BMI), and vascular disease [ 16 ]. Similarly in our study, we noted increasing proportion of patients with comorbidities such as hypertension, renal failure, cirrhosis, diabetes mellitus, obesity, and peripheral vascular disease in these hospitalizations ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prevalence of NASH cirrhosis and the components of metabolic syndrome, such as diabetes, hypertension, and dyslipidemia, were significantly higher in the GAVE group. 3 We conducted a similar retrospective study using a cohort of 941 patients with cirrhosis who underwent EGD for UGIB, ultimately dividing them into patients with GAVE (diagnosed endoscopically, with or without biopsy) and those with variceal bleed. We found that there was a significantly higher prevalence of obesity (measured via body mass index [BMI]), hypertension, diabetes mellitus, and NASH cirrhosis among the GAVE group (Table 1).…”
Section: Gave and Metabolic Syndromementioning
confidence: 99%
“…GAVE is strongly associated with chronic liver disease. In particular, 30% to 64% of individuals with GAVE have cirrhosis 1‐3 …”
mentioning
confidence: 99%
“…We read with great interest the work of Smith et al, 1 which examined the association between gastric antral vascular ectasia (GAVE) and metabolic syndrome. The study offers an intriguing perspective on GAVE as a potential manifestation of metabolic syndrome.…”
mentioning
confidence: 99%